1992
DOI: 10.2169/internalmedicine.31.625
|View full text |Cite
|
Sign up to set email alerts
|

Horseshoe Kidney and Membranous Glomerulonephritis with Cold Activation of Complement.

Abstract: A 48-year-old woman was admitted to our hospital because of proteinuria associated with persistent hypocomplementemia. Intravenous pyelography indicated the presence of horseshoe kidney without other abnormalities. Hypocomplementemia was caused by cold activation of complement. There were some findings suggestive of chronic liver disease (positive HCV antibody, hypergammaglobulinemia, low cholinesterase, etc.). Percutaneous renal biopsy showed the features of multiple evolutional phases of membranous glomerulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…It is frequently associated with anomalies of other systems in which genetic factors may play a common etiological role, including musculoskeletal, cardiovascular, and gastrointestinal systems, as well as in certain neurological conditions (23). The occurrence of glomerulonephritis in horseshoe kidney has already been reported (24)(25)(26)(27), with focal and segmental glomerulosclerosis described in two cases (25,27).…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently associated with anomalies of other systems in which genetic factors may play a common etiological role, including musculoskeletal, cardiovascular, and gastrointestinal systems, as well as in certain neurological conditions (23). The occurrence of glomerulonephritis in horseshoe kidney has already been reported (24)(25)(26)(27), with focal and segmental glomerulosclerosis described in two cases (25,27).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, temperature dependence seemed to explain the persistent, marked drops in haemolytic complement activity in our patients, while their clinical manifestations and laboratory parameters showed no evidence of active dysfunction. In addition, the fact that complement component C3 and C4 protein levels remained normal suggested that CDAC did not occur in vivo due to decreased synthesis and/or increased consumption, but did occur in vitro when sera were exposed to low temperatures [8][9][10][11][12][13][14]29,30]. CDAC was inhibited by EDTA because the latter acted as an anticoagulant agent as well as an inhibitor of the classical complement pathway by chelating such metal ions as Ca and Mg [7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…found five cases regarding horseshoe kidney in association with glomerulonephritis: membranoproliferative glomerulonephritis, [4] membranous glomerulonephritis, [5][6][7] and focal and segmental glomerulosclerosis. [8] The case with membranoproliferative glomerulonephritis was associated with cryoglobulinemic hepatitis C virus infection.…”
Section: Kayatas and Y üRünmentioning
confidence: 99%
“…One of the cases with membranous glomerulonephritis was associated with the cold activation of complement. [5] The remaining three cases were two patients with membranous glomerulonephritis, and one patient with FSGS was reported as idiopathic. [6][7][8] Vesicoureteral reflux, which can lead to focal segmental glomerulosclerosis, is a clinical condition commonly associated with horseshoe kidney.…”
Section: Kayatas and Y üRünmentioning
confidence: 99%